2014
DOI: 10.1016/j.bbr.2014.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic alcohol exposure impairs associative learning performance in adult zebrafish

Abstract: The zebrafish has been proposed for modeling fetal alcohol spectrum disorders (FASD). Previous FASD research with zebrafish employed high concentrations of alcohol and/or long exposure periods. Here, we exposed zebrafish eggs to low doses of alcohol (0, 0.25, 0.50, 0.75 and 1.0% (vol/vol); external bath application of which 1/20th may reach the inside of the egg) at 16-h post-fertilization (hpf) and only for a short duration (2 h) in the hope to avoid gross morphological aberrations and to mimic the more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 32 publications
1
49
2
1
Order By: Relevance
“…It is thus possible that although the dopaminergic neurons themselves may be intact, the development of their connectome is altered by embryonic alcohol exposure, and this alteration may explain the unresponsive nature of dopaminergic neurons to social stimuli. The intact nature of dopaminergic neurons and the possibility of abnormal ascending inputs to these neurons are also supported indirectly by finding unaltered motivation of embryonic alcohol exposed zebrafish to seek and obtain food in an associative learning task (Fernandes et al, 2014).…”
Section: Potential Mechanisms Underlying Embryonic Alcohol Exposure Imentioning
confidence: 78%
“…It is thus possible that although the dopaminergic neurons themselves may be intact, the development of their connectome is altered by embryonic alcohol exposure, and this alteration may explain the unresponsive nature of dopaminergic neurons to social stimuli. The intact nature of dopaminergic neurons and the possibility of abnormal ascending inputs to these neurons are also supported indirectly by finding unaltered motivation of embryonic alcohol exposed zebrafish to seek and obtain food in an associative learning task (Fernandes et al, 2014).…”
Section: Potential Mechanisms Underlying Embryonic Alcohol Exposure Imentioning
confidence: 78%
“…Individuals with FASD are known to have deficits in learning and memory 14 and zebrafish have been shown to recapitulate some of these deficits. 52,64,65 Associative learning in adult zebrafish has been shown to be impaired by a 2-h ethanol exposure starting at 16 hpf. 64 Carvan et al 52 found adult zebrafish that were exposed from 0 to 24 hpf to 0.06% and 0.18% ethanol took significantly more trial to predict the location of a food reward.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%
“…52,64,65 Associative learning in adult zebrafish has been shown to be impaired by a 2-h ethanol exposure starting at 16 hpf. 64 Carvan et al 52 found adult zebrafish that were exposed from 0 to 24 hpf to 0.06% and 0.18% ethanol took significantly more trial to predict the location of a food reward. However, Bailey et al 66 found that fish exposed to either 1% or 3% ethanol from either 8 to 10 hpf or 24 to 27 hpf did not have impaired spatial discrimination.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%
“…Fernandes et al, 2014; Bailey et al, 2015; and for a review see Cole et al, 2012 or Ali et al, 2011). However, the literature describing the acute effects of ethanol exposure during adolescence or adulthood on learning and memory in zebrafish is more modest.…”
Section: Cognitive Effects Of Psychoactive Drugs In Zebrafishmentioning
confidence: 99%